مؤشرات الاستدامة في المؤسسة الاقتصادية: مجموعة Bmwلصناعة السيارات نموذجا - بن قري, إلياس; زرزار, لعياشي (جامعة الوادي - University of Eloued, 2022)
Sustainability is one of the most important objectives of the economic enterprise and BMW has achieved the first position in achieving sustainability Through this study, the sustainability indicators (economic, environmental and social) will be determined and from it the following question will posed : What are the indicators of the sustainability of the economic institution approved in the BMW Group for the automotive industry ? The analysis of the sustainability indicators in the BMW Group led us to confirm that the group is entitled to the first place, since it produces environmentally friendly electric cars, which record a significant increase in sales in addition to using renewable resources in all its operations and it employs different groups of society in different ways age and gender in different positions
Sustainability indicators in economic companies case of BMW group for the automobile industry
مقال
Keywords: مؤشرات؛ استدامة؛ المؤسسة الاقتصادية; BMW.